Technology of integration of expressive means in the chinese musical drama kunqu in its parallels to the liturgical mystery drama of europe (Pedagogy of Higher and Secondary Education, 2009)
The Chinese music drama Kuncyuy in her parallel to liturgical drama - of Europe. The Article illuminates the questions history metaphysicians on example of the parallelismartistic event 15-16 ages upon their urgency for modem listeners.
Keywords: Chinese music drama Kuncyuy; liturgical drama; historical metaphysics